The role of zoological gardens in environmental education - Valerie Howard (Southern African Journal of Environmental Education, 1988)
This article attempts a broad survey of the environmental programmes offered at both the formal educational and informal recreational levels by zoos in Johannesburg, London, Whipsnade Park, Bristol and San Diego, California. It describes the part that zoos play in imparting knowledge of environmental conservation and an understanding of its importance.